Sustainability Dimensions and Organic Farming – A Case Analysis of Organic Cardamom (Elettaria cardamomum) Growers in Kerala State of India (Indian Journal of Extension Education, 2021)
Sustainability concerns about organic farming is a sector of prime importance in every nation, that aims to make agriculture economically viable, ecologically sound, equitable, culturally appropriate, and grounded on holistic science. This study was conducted in the spice garden of the Kerala state-Idukki which contributes a large amount to the export basket in India. More than that, this sector contributed largely to the economic development and employment generation in the area. The study identified that along with the ecological sustainability of the organic cultivation practices, farmers were more oriented to the economic and social sustainability of the organic way of cardamom production due to the social and cultural linkage which the crop possessed in the study area. The study revealed that organic cardamom production has enormous potential for improving the sustainability of agriculture practices followed and suggests that organic cardamom farming should receive prime attention from all stakeholders to realize its full potential in socio-economic dimensions along with the environmental sustainability concerns which it offers in agriculture.